Only benign encounters? The Sami, Wehrmacht, the secret police services and Lebensborn in the North Calotte at war, 1940–1944 - Nyyssönen, Jukka (Pohjois-Suomen Historiallinen Yhdistys ry, 2021)
This article sheds new light on previous perceptions of good relations between the occupant forces and the Sami minority in Finland and Norway between 1941 and 1944. The preconditions and varieties of relations and encounters are researched: those relating to the Gestapo and to Valpo, the Finnish state police, as well as to the Lebensborn. Sources utilized consist of archival material produced by the Wehrmacht and by Finnish organizations responsible for cooperation between the troops and Finnish administration (Yhteysesikunta Roi, liaison staff Roi), by the Finnish State Police and by the Lebensborn. This article charts relations within institutional contexts, where more aggressive encounters would be expected to surface. Even though the encounters were mostly benign, and German-Austrian discourse on the Sami lacked any de-humanizing aggression, the Sami were nonetheless exposed to a racializing and eugenic gaze and practices in some institutional contexts. In addition, the Sami were treated as a suspicious factor that needed to be kept an eye on, like other civilian groups in the rear area.